2015
DOI: 10.1039/c5cp00916b
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study on the magnetic properties of nonmetal atom doped phosphorene monolayers

Abstract: In order to induce magnetism in two-dimensional semiconductors for their applications in spintronic devices and novel chemical and electronic properties of semiconducting phosphorene, the geometrical structure, electronic and magnetic properties of doped phosphorene monolayers with a series of nonmetal atoms, including H, F, Cl, Br, I, B, C, Si, N, As, O, S and Se, were systematically investigated using first-principles calculations. The results show that although the substitutional doping of H, F, Cl, Br, I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…Interestingly, magnetic moment can also be induced by nonmagnetic dopants such as O, S, Se, C, Si, etc. in black phosphorus as well as blue phosphorus …”
Section: Spin Generationmentioning
confidence: 99%
“…Interestingly, magnetic moment can also be induced by nonmagnetic dopants such as O, S, Se, C, Si, etc. in black phosphorus as well as blue phosphorus …”
Section: Spin Generationmentioning
confidence: 99%
“…Aside from electronics applications, phosphorene is of interest in the fields of chemistry and biomedical engineering for application as gas sensors, medical imaging agents, photothermal therapy, and drug delivery . In the field of physics, phosphorene has been applied in mechanics, thermal physics, acoustics, nonlinear optics, photonics, electronics, photoelectronics, thermoelectronics, spintronics, magnetics, and electromagnetics . In material sciences, phosphorene can be used as functional flexible substrates and electrical enhanced composites .…”
Section: Introductionmentioning
confidence: 99%
“…Since pristine phosphorene is a nonmagnetic semiconductor, it cannot be directly used in the field of spintronics, however, different strategies such as edge cutting structures [18][19][20][21][22], doping with non-magnetic adatoms [23][24][25], or atomic defects (vacancies and adatom adsorption) [17,26,27] have been suggested to induce magnetic behaviors in phosphorene. For instance, it is found that due to the magnetic instability induced by the halffilled edge bands crossing the Fermi level, phosphorene nanoribbons (PNRs) with bare zigzag edges are antiferromagnetic semiconductors [19].…”
Section: Introductionmentioning
confidence: 99%